2016
DOI: 10.1128/aac.03101-15
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Escherichia coli Strains Isolated from Retail Meat That Harbor bla CTX-M and fosA3 Genes

Abstract: A total of 55 cefotaxime-resistant Escherichia coli isolates were obtained from retail meat products purchased in Shenzhen, China, during the period November 2012 to May 2013. Thirty-seven of these 55 isolates were found to harbor a bla CTX-M gene, with the bla CTX-M-1 group being the most common type. bla CMY-2 was detected in 16 isolates, alone or in combination with other extended-spectrum ␤-lactamase (ESBL) determinants. Importantly, the fosA3 gene, which encodes fosfomycin resistance, was detected in 12 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 42 publications
3
27
1
Order By: Relevance
“…Several reports have indicated that the transfer of CTX-M mobile plasmids could be frequently accompanied by the acquisition of fosfomycin resistance genes. 53,54 In our study, 17 carbapenem-resistant strains harboring CTX-M plasmids were positive for the fosA3 gene. Colistin resistance represents another health concern.…”
Section: Discussionmentioning
confidence: 57%
“…Several reports have indicated that the transfer of CTX-M mobile plasmids could be frequently accompanied by the acquisition of fosfomycin resistance genes. 53,54 In our study, 17 carbapenem-resistant strains harboring CTX-M plasmids were positive for the fosA3 gene. Colistin resistance represents another health concern.…”
Section: Discussionmentioning
confidence: 57%
“…Another study described a high prevalence of FosA3-producing E. coli in pets and their owners, highlighting the transmission of fosfomycin-resistant E. coli isolates between humans and animals (164). Another Chinese study described the fosA3 gene in E. coli from fresh pork and chicken meat (165). In that study, the fosA3 gene was often found together with ESBL genes (bla CTX-M-55 , bla CTX-M-15 , or bla CTX-M-123 ) on plasmids of 78 to 138 kb in size.…”
Section: Resistance To Fosfomycinmentioning
confidence: 99%
“…Urinary tract infection (UTI) is one of the most common community-acquired infections [4][5][6] , and fosfomycin has become one of the potent antimicrobials in treatment of Gram-negative bacterial infections 135) including UTI 136,137) due to the recent rapid increase in the prevalence of ESBL-producing and fluoroquinolone-resistant E. coli in the community as well as in clinical settings worldwide 15,17) . However, the plasmid-mediated fosfomycin resistance gene, fosA3, has emerged 138) and spread in both human and animal in several Asian countries [139][140][141] , especially in China [142][143][144] . This might owe to heavy use of fosfomycin in livestock farming environments in some countries.…”
Section: Co-transfer Of Esbl Genes With Other Antimicrobial Resistancmentioning
confidence: 99%